THU0293 B-cell responses to type I interferon define disease activity in SLE and can be measured by cell surface tetherin (CD317). (15th June 2017) - El-Sherbiny, YM; Yusof, MY Md; Psarras, A; Hensor, E; Tooze, R; Doody, G; Wittmann, M; Emery, P; Vital, EM
Abstract : Background: SLE is a Type I interferon (IFN-I) mediated disease with autoreactive B cells. Whole blood interferon-stimulated gene (ISG) expression is used to measure IFN-I status but does not consistently correlate with clinical features and therapy response. ISG expression may be influenced by differing response in individual cell subsets as well as IFN-g. Tetherin is a cell surface protein encoded by the interferon-stimulated gene BST2 . Objectives: To evaluate tetherin expression as a novel cell-specific flow cytometric biomarker for IFN-I response. Methods: In vitro, we tested response of expression of BST2 and 30 other ISGs to stimulation with IFN-a and IFN-g, as well as dose response of BST2 and tetherin protein in B cells. Sorted cells (Monocyte, T, NK, naïve and memory B, plasmablast) from 8 controls and 10 SLE patients were used to test variation in expression of 31 ISGs between cell subsets and whether tetherin measured by flow cytometry is a cell specific marker for IFN-I response. Samples from 156 SLE patients, 30 ACPA+ANA- RA (DAS28>3.2) patients and 22 healthy controls (HC) were used in 3 clinical validation studies of tetherin vs. ISG score against diagnosis, disease activity (BILAG-2004) and plasmablast repopulation after rituximab. Results: Some ISGs' expression in B cells increased in response to both IFN-a and IFN-g. Others, which included BST2, were selective for IFN-a. An 18-gene ISG score derived from this latter group was calculated for comparison with tetherin. Results from cell sorting showed that ISG Score was highest in monocytes; other subsets were 75–85% lower (p<0.001). SLE-associated increase in expression (SLE:HC ratio) varied between 2.56 (T cells) to 4.93 (plasmablasts). Diagnosis: ISG score differentiated HC from SLE with ratio 3.58 (1.94 – 6.61) and large effect size 0.14 (partial eta squared). Using tetherin for cell specific IFN response revealed marked differences between subsets. Monocytes did not differentiate HC and SLE at all with ratio 1.19 (0.87 – 1.61) and effect size 0.03. Memory B cells had medium-large effect size of 0.11 with ratio 1.59 (1.21 – 2.09). Comparing SLE and RA the largest effect size was for plasmablast Tetherin at plasmablasts at 0.23, with ratio 2.20 (1.66 – 2.93). Disease activity: ISG score was associated with cutaneous disease activity (BILAG A/B) but not musculoskeletal (Fig 1 ). Monocyte tetherin was associated with musculoskeletal disease activity but not cutaneous. Memory B cell tetherin was associated with disease activity in both these organs. Memory B cell tetherin was increased with renal (p=0.005) or haematological (p=0.005) activity with no differences in ISG score for these domains (p=0.152, p=0.989 respectively). Plasmablast numbers after rituximab were associated with Memory B cell tetherin (R=0.38, p=0.047) but not ISG score (R=0.24, p=0.219). Conclusions: ISG expression in unsorted blood is influenced by IFN-g and cellular composition of the sample as well as IFN-I. Flow cytometric measurement of surface tetherin is a cell-specific assay for IFN-I that avoids these problems. Memory B cell tetherin was better associated with plasmablast numbers and clinical features of disease than monocyte tetherin or ISG score. Disclosure of Interest: None declared